2009
DOI: 10.1111/j.1533-2500.2008.00254.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Pulsed Radiofrequency Treatment for Chronic Benign Pancreatitis Pain

Abstract: Current analgesic strategies for the management of pain caused by chronic benign pancreatitis are poorly defined and frequently unsuccessful. Strategies have included pharmacotherapy, surgery, and interventional pain techniques such as celiac plexus blockade. Persistent quality analgesia with acceptable side effect profiles is difficult to achieve. Pulsed radiofrequency treatment is a minimally neurodestructive technique that may alter nerve conduction and offer a reduction in pain perception. We describe our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Pulsed radiofrequency (PRF) is a relatively new technique that is increasingly used in treatment of chronic pain. It can be applied in many clinical situations and has been recommended for treatment of trigeminal neuralgia, headaches, cervical pain, lumbar pain, sympathetic maintained pain, malignant pain, peripheral neuropathic pain, chronic benign pancreatitis, residual limb pain, and phantom limb pain . It is a minimally invasive technique that involves application of electric fields to nerves to inhibit nociceptive stimuli and prevent pain transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed radiofrequency (PRF) is a relatively new technique that is increasingly used in treatment of chronic pain. It can be applied in many clinical situations and has been recommended for treatment of trigeminal neuralgia, headaches, cervical pain, lumbar pain, sympathetic maintained pain, malignant pain, peripheral neuropathic pain, chronic benign pancreatitis, residual limb pain, and phantom limb pain . It is a minimally invasive technique that involves application of electric fields to nerves to inhibit nociceptive stimuli and prevent pain transmission.…”
Section: Introductionmentioning
confidence: 99%
“…22 It is also hypothesized that PRF ablation may work by disrupting nerve conduction and thereby interrupting pain signaling pathways while maintaining the integrity of the neural structures. 23 In 2009, Brennan and colleagues reported the results of 2 patients with chronic pancreatitis that was successfully treated with PRF. 23 In their report, the splanchnic nerves were treated bilaterally at the T12 level.…”
Section: Discussionmentioning
confidence: 97%
“…23 In 2009, Brennan and colleagues reported the results of 2 patients with chronic pancreatitis that was successfully treated with PRF. 23 In their report, the splanchnic nerves were treated bilaterally at the T12 level. In our case, we elected to treat bilaterally at the T12 and L1 levels with the hope that the additional treatment sites would result in greater clinical effects and longer duration of relief.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The use of pulsed radio-frequency ablation of the splanchnic nerves has been described as an alternative to splanchnic neurolysis for the treatment of pancreatic and upper abdominal pain [20][21][22] . Raj et al [ 21 ] reported that up to 40% of patients had excellent pain relief after a thoracic splanchnic nerve block, with only 15% of patients reporting poor results in a series of 107 patients with abdominal pain [ 21 ] .…”
Section: Splanchnicmentioning
confidence: 99%